2020
DOI: 10.1021/acsomega.0c01950
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Understanding of the Staging Properties of the Graphite Intercalation Compounds towards Dual-Ion Battery Applications

Abstract: Graphite-based dual-ion batteries are a promising alternative to the lithium-ion batteries for energy storage because of its potentially lower cost, higher voltage, and better safety. Among the most important materials in the dual-ion battery are the graphite and graphite intercalation compounds (GICs), whose properties determine the performance of electrodes. The GICs are formed at both anode and the cathode sides during the charging process in which the graphene sheets and the intercalants are arranged in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 58 publications
2
25
0
1
Order By: Relevance
“…Such multiple stages of the aluminate ion insertion process is well documented for graphitic materials, which possess similar layered structures. 54,55 This apart, a prominent pair of red-ox peaks in the potential range of ca. 1.8−2.2 V might possibly be attributed to the partial change in the Mo-oxidation states from Mo 4+ to Mo 5+ state and back, possibly owing to the partial lattice insertion of Al 3+ ions.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Such multiple stages of the aluminate ion insertion process is well documented for graphitic materials, which possess similar layered structures. 54,55 This apart, a prominent pair of red-ox peaks in the potential range of ca. 1.8−2.2 V might possibly be attributed to the partial change in the Mo-oxidation states from Mo 4+ to Mo 5+ state and back, possibly owing to the partial lattice insertion of Al 3+ ions.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…where E(anion:C 24n ), E(C 12 ), and E(anion) are the DFT total energies of anion-GICs, AB-stacking graphite, and isolated anions in a supercell, respectively. Anion in eqn (2) denotes a neutralized anion near graphite electrodes, 24,25 and the solution stabilization of anions was neglected since the water/ lithium ratios were relatively small (about 2.7 and 2.8 in the solutions of 5.2 M LiTFSA and 7.9 M LiOTf, respectively) and TFSA and OTf anions were not strongly coordinated with water molecules in aqueous highly concentrated solutions.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…In addition, Zhou and Sit reported a large variety of formation energies of anion-GICs using DFT calculations: ClO 4 -GIC 4 AlCl 4 -GIC TFSA-GIC 4 BF 4 -GIC 4 PF 6 -GIC. 25 We also calculated the formation energies of GICs with TFSA and OTf anions and found that TFSA-GICs were more stable than OTf-GICs: À0.96 eV for C 24 TFSA (stage 2) and À0.48 eV for C 24 OTf (stage 2). Optimized structures of stage 2 GICs of TFSA and OTf are illustrated in Fig.…”
Section: Affinity Of Anions For Gic Formationmentioning
confidence: 99%
“…By applying proper electrochemical (EC) potentials, solvated ClO4and HSO4ions percolate between the HOPG layers. HOPG thus evolves into the so-called graphite intercalated compound (GIC), which shows different transport properties with respect to the pristine sample [13][14][15]. In addition, the presence of ions within the interlayer spacing of graphite helps its delamination in liquid-phase [16].…”
Section: Introductionmentioning
confidence: 99%